Induction of larval settlement in crown-of-thorns starfish is not mediated by conspecific cues - Peter C. Doll; Sven Uthicke; Ciemon F. Caballes; Frances Patel; Maria del C. Gomez Cabrera; Bethan J. Lang; Morgan S. Pratchett (Scientific Reports, 2023)
Abstract Population irruptions of crown-of-thorns starfish (COTS; Acanthaster spp.) remain a major cause of coral reef degradation throughout the Pacific and Indian Oceans and are inherently modulated by larval settlement and recruitment success. Gregarious larval settlement, as exhibited by many other ecologically important marine invertebrates, can catalyse population growth and replenishment. However, whether conspecific cues induce or influence the settlement of COTS larvae remains a critical information gap. This experimental study examined the induction of COTS settlement in response to a range of conspecific cues associated with early- and late-stage herbivorous juveniles, corallivorous juveniles and adults. Competent COTS larvae were generally not induced to settle by the presence of conspecifics or cues associated with conspecifics, while the settlement success of COTS in the presence of coralline algae was not inhibited or enhanced by adding conspecific conditioned seawater. Rather than being reinforced by gregarious settlement, the recruitment of COTS populations appears dependent on associative settlement cues (i.e., coralline algae and/or associated microbial communities) signalling suitable benthic habitat.